2001
DOI: 10.1136/fn.84.2.f106
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry, severe retinopathy, and outcome at one year in babies of less than 28 weeks gestation

Abstract: Aim-To determine whether diVering policies with regard to the control of oxygen saturation have any impact on the number of babies who develop retinopathy of prematurity and the number surviving with or without signs of cerebral palsy at one year. Methods-An examination of the case notes of all the 295 babies who survived infancy after delivery before 28 weeks gestation in the north of England in 1990-1994. Results-Babies given enough supplemental oxygen to maintain an oxygen saturation of 88-98%, as measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
270
4
14

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(296 citation statements)
references
References 31 publications
8
270
4
14
Order By: Relevance
“…40 At the time of these prospective studies, there were surveys or cohort studies that also supported an association with less ROP in different centers utilizing different SpO2 targets. [41][42][43] Recently, several studies [44][45][46] have confirmed our findings. Wright et al 44 concluded that SPO 2 between 83 and 93% and avoiding oxygen fluctuations prevent the early vaso-obliterative phase and subsequent severe ROP.…”
Section: Tension Of Arterial Oxygen (Pao 2 )supporting
confidence: 87%
“…40 At the time of these prospective studies, there were surveys or cohort studies that also supported an association with less ROP in different centers utilizing different SpO2 targets. [41][42][43] Recently, several studies [44][45][46] have confirmed our findings. Wright et al 44 concluded that SPO 2 between 83 and 93% and avoiding oxygen fluctuations prevent the early vaso-obliterative phase and subsequent severe ROP.…”
Section: Tension Of Arterial Oxygen (Pao 2 )supporting
confidence: 87%
“…Although the precise oxygen saturations to avoid remain unknown, avoiding hyperoxia, and particularly avoiding swings between hyperoxia and hypoxia, in the first few weeks of life has been shown to decrease the severity of ROP Askie and Henderson-Smart, 2000;Tin et al, 2001;Chow et al, 2003;Anderson et al, 2004;York et al, 2004). The relationship between hyperoxia and subsequent neovascularization appears more complex than suggested previously.…”
Section: Implications For Prevention and Treatment Of Ropmentioning
confidence: 98%
“…Implementation of these guidelines appears to have reduced the incidence of ROP. [5][6] At the beginning of 2004, our neonatal intensive care unit instituted new oxygen saturation guidelines with a targeted range of 90-96% for infants ≤ 30 weeks gestational age at birth. Before then, oxygen saturation levels were generally kept in the upper 90's.…”
Section: Introductionmentioning
confidence: 99%